2021
DOI: 10.1097/md.0000000000028488
|View full text |Cite
|
Sign up to set email alerts
|

Real life use of dolutegravir doravirine dual regimen in experienced elderly PLWH with multiple comorbidities and on polypharmacy

Abstract: By increasing life expectancy of people living with HIV, the most clinical challenge is managing both drug-to-drug interactions and comorbidities (especially metabolic). Doravirine (DOR), a new non-nucleoside reverse transcriptase inhibitor, recently approved for the treatment of HIV, could be a good companion of dolutegravir (DTG) in a dual regimen for experienced elderly patients with multimorbidity and polypharmacy. We herein report our preliminary experience in a small cohort of elderly patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Our single-center service evaluation of small numbers of PWH found that dolutegravir and doravirine alone or in combination with other antiretrovirals appeared safe and achieved virologic suppression in most recipients, consistent with the prior case series of PWH receiving dolutegravir plus doravirine. 7 Our experience underscores the importance of close longitudinal follow-up in PWH receiving less studied ART combinations to detect potential adverse effects, especially in older populations with multiple comorbidities. Larger randomized longitudinal research studies such as the planned Efficacy of Doravirine + Dolutegravir Dual Therapy in the Context of Antiretroviral Therapy Switch (DORDOL) study will assess durability of virologic suppression and inform future clinical guidance regarding this ART combination.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our single-center service evaluation of small numbers of PWH found that dolutegravir and doravirine alone or in combination with other antiretrovirals appeared safe and achieved virologic suppression in most recipients, consistent with the prior case series of PWH receiving dolutegravir plus doravirine. 7 Our experience underscores the importance of close longitudinal follow-up in PWH receiving less studied ART combinations to detect potential adverse effects, especially in older populations with multiple comorbidities. Larger randomized longitudinal research studies such as the planned Efficacy of Doravirine + Dolutegravir Dual Therapy in the Context of Antiretroviral Therapy Switch (DORDOL) study will assess durability of virologic suppression and inform future clinical guidance regarding this ART combination.…”
Section: Discussionmentioning
confidence: 81%
“…10 The prior case series of dolutegravir with doravirine in older PWH noted ART simplification as a factor in 69% and polypharmacy in all participants. 7 Dolutegravir and doravirine combinations avoid the drug interaction challenges of cobicistat- or ritonavir-boosted protease inhibitor containing regimens and may mitigate risks from polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is consistent with other studies, in whom the main reasons for the switch were high cardiovascular/metabolic risk, treatment simplification, drug-to-drug interaction and toxicity. [14][15][16] This suggests that clinicians look at DOR as a drug useful to improve the management of metabolic issues in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the use of this new NNRTI in a real-life setting are still scarce, [14][15][16] and it is important to define how clinicians have interpreted the role of DOR in the current HIV armamentarium. Therefore, this study aimed to describe the reasons leading clinicians to switch patients to a DOR-containing regimen and its role in clinical practice.…”
Section: Fc Is Principal Investigator (Honorary) In Clinical Studies ...mentioning
confidence: 99%